Reaction Of Barley Genotypes To Bipolaris Sorokiniana (Bangladesh Journal of Agricultural Research, 2011)
A study on response of 29 barley genotypes resistant to Bipolaris leaf blight (Bipolaris sorokiniana) was conducted to investigate the relationship of the components of resistance of 29 barley genotypes. Data on five components of resistance viz., infection frequency (number of lesions per plant), lesion size (mm2), percent leaf area affected by lesion, percent necrotic area on leaf, and disease severity were recorded as components of resistance. The genotypes fall into four clusters. Cluster I was to be the largest having 11 genotypes which was followed by cluster III, IV, and II. Considering the overall mean performances of different clusters, genotypes of cluster II showed better performance against resistance. From the cannonical variate analysis, it was found that three components like lesion size, necrosis, and 100-seed weight were found positive for the both vector, and these characters contributed maximum towards the divergence for disease development of the barley accessions.   Keywords: Bipolaris sorokiniana; barley; leaf blight DOI: http://dx.doi.org/10.3329/bjar.v36i1.9236 BJAR 2011; 36(1): 123-128